The testing for COVID-19 in symptomatic patients as a protective factor against stress, anxiety, and depression - Alan Chaves dos Santos; Paula Jaeger Tenorio; Elias Almeida S. Barbosa; Gustavo Fonseca de Albuquerque Souza; Gabriela Albuquerque Souza; Gabriella de Almeida Figueredo Praciano; Laura Brito Barreto Maranhão; Gabriela Oliveira Lobo Pereira da Costa; Alex Sandro Rolland Souza
Abstract Objectives: to determine the frequency of stress, anxiety, and depression symptoms in symptomatic patients for COVID-19. To evaluate the associated factors involved in these variants. Methods: between May/June of 2020, it was conducted a prospective cross-section study with symptomatic participants for COVID-19 (n=300). It was applied an online questionnaire and the DASS-21 to evaluate the mental health of participants. Results: it was observed that 28.6%, 29.7% and 27% of the participants showed severe/extreme levels symptoms of stress, anxiety, and depression, respectively. The testing for COVID-19 application had constituted a protective factor for the development of psychiatric morbidity, once it had shown significant association in the low frequencies of severe/extreme depression [Odds Ratio (OR)]= 0.26; p=0.002) and stress (OR=0.39; p=0.01). Conclusion: individuals that are symptomatic for COVID-19 are a vulnerable group that may present high symptomatology for depression, anxiety, and stress. The identification of psychiatric morbidity frequency and its associated factors may contribute for the development of mental health strategies aiming at the prevention and mitigation of psychological impact in COVID-19 symptomatic population during the pandemic.